Playing With Boiardo. On a Comic Rewriting of the "Inamoramento de Orlando" (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2023)
The rewriting in the form of a graphic novel of Orlando innamorato, promoted in 2021 by the Centro Studi Matteo Maria Boiardo, takes up the challenge of bringing the poem closer to an audience - young people of the 2000s - not accustomed to reading Renaissance chivalric literature, but ready to rediscover the emotion, surprise and wonder hidden in the deeds of the paladins. An attempt which, looking at the comic rewritings of the great epic poems and at the work of Gianni Celati, required an immersion in Boiardo’s text in order to untie, sift and weave the threads of the narrative again to tell Orlando’s «bella istoria» to a new audience.
Keywords: Boiardo; Orlando innamorato; graphic novel; Gianni Celati